Using PFG‐NMR and iGC to Study Diffusion and Adsorption in Heterogeneous Catalysts - Thompson, Emma S.; Graf, Katja; Brendlé, Eric; Schreyer, Hannah; De Baerdemaeker, Trees; Parvulescu, Andrei‐Nicolae; Kellermeier, Matthias (ChemCatChem, 2024)
Mass transport in porous systems is inherently complex, but at the same also of utmost importance for large‐scale industrial processes such as heterogeneous catalysis. For each of the different length scales of diffusive motion potentially involved or relevant, specific characterization techniques have been developed and successfully applied over the years – including, but not limited to pulsed field gradient nuclear magnetic resonance (PFG‐NMR) spectroscopy, zero length column (ZLC) measurements and inverse gas chromatography (iGC). While each of these methods can deliver detailed information on certain types of diffusion, none of them are capable of delivering a full picture of mass transport across multiple length scales alone. In this context, the goal of the present work was to evaluate the technical feasibility and characterization potential of the hyphenated combination of PFG‐NMR and iGC in a coupled experimental setup. Challenges, advantages, and limitations of this approach are discussed using the example of propane adsorption and diffusion in two different zeolite catalysts (Mg(H)‐ZSM‐5 and Silicalite‐1). It is shown that the simultaneous detection of self‐diffusion on short length scales (as probed by PFG‐NMR) and transport diffusion covering longer distances (detectable by iGC) cannot be realized under the used conditions, essentially due to the lack of kinetic control at higher reactant loadings. The key advantage of the developed coupled setup is the ability of the iGC instrument to provide defined and readily variable levels of catalyst loading, which enables advanced pore connectivity studies by PFG‐NMR and yields thermodynamic data on reactant adsorption at the same time. By using a hyphenated setup comprising pulsed‐field gradient (PFG) NMR spectroscopy and inverse gas chromatography (iGC), diffusion in zeolite catalysts can be conveniently measured at various degrees of loading with gaseous reactant molecules, while monitoring their subsequent desorption yields thermodynamic information such as adsorption isotherms.